THE ECONOMIC ESSENCE, IMPORTANCE, TYPES, AND SOURCES OF FINANCING OF INVESTMENTS (International journal of artificial intelligence, 2025)
The article explores the economic essence and significance of investments as a key factor in ensuring sustainable economic development. Investments are analyzed as a crucial mechanism for expanding production, improving competitiveness, and fostering innovation in various sectors of the economy. The study classifies the main types of investments — real, financial, intellectual, and social — and provides insights into their distinctive features and functions. Special attention is given to the sources of investment financing, including internal (own funds, depreciation, profit) and external (bank loans, state funds, foreign direct investments, and securities markets) sources. The article also highlights the role of investment policy in creating a favorable investment climate and in supporting the balanced growth of national and regional economies. The findings underscore that the effective use and management of investment resources directly determine the pace of economic modernization and social welfare.